Introduction: Culture, sustainable development and social quality: A paradigm shift in the economic analysis of cultural production and heritage conservation. Issue 2 (June 2016) - Bertacchini, Enrico; Segre, Giovanna
Abstract: The aim of the special issue is to address the changing paradigm that the economic analysis of cultural production and heritage preservation has undergone in the last decade, with a particular emphasis on the cultural economic perspective. New emphasis on the role of creativity in society, the spread of the digital revolution and the reconsideration of culture and heritage as drivers of sustainable development and social quality are radically changing the analytical perspectives and research agenda. The selection of papers, involving some of the leading cultural economic scholars, present several dimensions of such evolving pattern. Highlights: The special issue addresses the changing paradigm in cultural economics. Previous literature has mainly focused on public and welfare economic approaches. Instrumental value is replaced by social quality and sustainable development dimensions.